Displays and breeding behaviour of captive Ringed Teal Callonetta leucophrys - Brewer, G L (Wildfowl, 2001)
Observations of captive Ringed Teal allowed several previously undescribed displays to be noted, including specialized displays for maintaining contact, reinforcing the pairbond and biparental care. Males and females gave loud calls during female-only and pair flights that were associated with nest searching, Pair bonds were reinforced by bouts of contact calling when pairs became separated, and mates and family members greeted each other and came together in group displays after aggressive encounters. Males defended their mates throughout the breeding season, including during forced extra pair copulation attempts. Males did not consistently defend nest boxes. Females defended a nest box only when they physically occupied it, laid eggs in more than one box, and were the only sex to incubate. One pair re-nested when their ducklings were about four weeks old. Both mate and female parents performed Distraction Displays and called to ducklings when they became separated from the brood. A preliminary comparison suggests similarities between Ringed Teal and four closely-related species for displays associated with nest searching and pairbond maintenance, including possible homologies for female vocalizations. Differences were noted in male vocalizations, female inciting behavior, copulatory displays, and family displays, but further information on these species and wild Ringed Teal is needed to investigate possible convergence or phylogenetic influences.